Unemployment rate and economic cycle in Peru 1971-2013 - García Sandoval, Carlos (2014)
The objective of this study is to evaluate the importance of unemployment in Peru from the perspective of the so-called "Okun's Law", reviewing the effectiveness of economic policies and the legal framework and institutional arrangements in force in Peru in the labor market. The research aims to evaluate the scope of the so-called "structural adjustment", initiated in the 1990s, from the point of view of workers' employability and, above all, its impact on GDP growth. The latter is relevant because it involves the quality of life of the population (and the efforts to fight poverty), which strongly depend on the potential employability of workers.